PENGARUH STRATEGI MATHEMATICAL HABITS OF MIND MHM BERBASIS MASALAH TERHADAP KREATIVITAS SISWA - Ali Mahmudi; Utari Sumarmo (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Effects of the Problem-Based MHM Strategy on the Mathematical Creative Thinking Ability and Perception of Creativity. This paper presents findings from a quasi-experimental study with a static group comparison design by using the problem-based MHM instructional strategy conducted to investigate students’ mathematical creative thinking ability (MCTA) and perception of creativity (PoC). The study involved 126 students from two junior high schools of high and middle categories in Yogyakarta. The instruments were a test of Mathematical Prior Ability (MPA), a test of MCTA, and a scale of PoC. The data were analyzed using the two-way ANOVA and Chi-Square test. The study found that the problem-based MHM instructional strategy was able to improve students’ MCTA better than the conventional instruction, there was association between MCTA and PoC, there was an interaction between the school category and the instructional category on PoC, and there was no such interaction on MCTA. Keywords: problem-based MHM instructional strategy, mathematical creative thinking ability, perception of creativity